Care bundles: implementing evidence or common sense? - Camporota, Luigi (BioMed Central, 2011)
Care bundles aim to improve standard of care and patient outcome by promoting the consistent implementation of a group of effective interventions. However, a variety of barriers prevent their full application in clinical practice. Here, we discuss some of the benefits and limitations of care bundles in the delivery of safer and more effective and consistent health care.